Adoption and farmer’s perceptions of BARI Aam-3 Mango variety in selected areas of Bangladesh (Research in Agriculture Livestock and Fisheries, 2018)
The study was conducted to assess the level of BARI Aam-3 mango variety adoption, factors affecting adoption and farmer’s perceptions about this variety in four districts namely Khagrachori, Bandorban, Naogaon, and Satkhira of Bangladesh during February to March, 2018. A total of 128 BARI Aam-3 growers and 72 non-growers were selected using multi-stage random sampling technique. Logit model was used to assess the determinants of adoption. The study revealed that BARI Aam-3 was the most adopted variety (57%) than other and it covered 47.5% of the total mango production in the study areas. Most of the rice and vegetable fields are occupied by BARI Aam-3 and majority of the respondents practiced intercropping with BARI Aam-3. Family size, sex, training, and extension linkage had significant positive effect on adoption of BARI Aam-3 mango variety while age and farm size had negative effect. Three fourth (75%) of the respondents collected information about this variety from other neighbor farmers while about 43% learned from Department of Agricultural Extension office. More than half of the respondents (63%) have strong ambition to enlarge their BARI Aam-3 mango variety orchard in the future for its unique features such as non-alternate bearing and early fruiting. Climate change, price fluctuation, higher labour costs and access of Indian mango to the market prior releasing this variety were the major bottlenecks for wider adoption of this variety. The study concluded that there is an urgent need to create a sustainable market environment to ensure a better market price for the mango growers. In addition, training and extension services need to expand all over the country to increase the rate of adoption of BARI Aam-3 mango variety.Res. Agric., Livest. Fish.5(3): 301-311, December 2018